THE LEVEL OF IMPLEMENTATION OF ISOK MANGANESE INNOVATION TOWARDS THE DEVELOPMENT OF SOCIAL WELFARE IN THE CITY OF SURABAYA - suhendra vmi, adi (Jurnal Studi Inovasi, 2025)
This research is about the level of implementation of the Innovation in Providing Daily Meals for the Poor and Neglected, Community Empowerment in Food Activities (ISOK MANGAN) towards the development of social welfare in the City of Surabaya . ISOK MANGAN Innovation is the provision of daily food for the poor and neglected so that they can obtain a healthier life and more decent food. Providing food for the poor and neglected can foster a spirit of mutual cooperation and empathy in the community, caring for those around them and can fulfill basic needs in the form of food for the elderly, orphans, and people with disabilities in the city of Surabaya. This study uses a qualitative approach research method. The data collection technique uses a literature review . A literature review is a systematic examination of critical scientific literature in analyzing, evaluating, and synthesizing research findings, theories, and practices . Literature review provide an overview of the development of a particular topic. The results of innovation ISOK MANGAN is a program that provides healthy food assistance once a day throughout the year for the poor and neglected. ISOK MANGAN not only fulfills the food needs of the poor but also stimulates the people's economy. The provision of food is entrusted to local residents. Food management is carried out by community groups such as Nursing Homes, Community Social Workers Associations, and Orphanages. This innovation has a chain of benefits that can be felt by the entire community. The social network within it strengthens togetherness, instills a social spirit, and can stimulate the people's economy.